2012
DOI: 10.1158/1078-0432.ccr-11-0880
|View full text |Cite
|
Sign up to set email alerts
|

Costimulatory Protein 4IgB7H3 Drives the Malignant Phenotype of Glioblastoma by Mediating Immune Escape and Invasiveness

Abstract: Purpose: Recent work points out a role of B7H3, a member of the B7-family of costimulatory proteins, in conveying immunosuppression and enforced invasiveness in a variety of tumor entities. Glioblastoma is armed with effective immunosuppressive properties resulting in an impaired recognition and ineffective attack of tumor cells by the immune system. In addition, extensive and diffuse invasion of tumor cells into the surrounding brain tissue limits the efficacy of local therapies. Here, 4IgB7H3 is assessed as … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
113
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(127 citation statements)
references
References 38 publications
11
113
1
2
Order By: Relevance
“…The growth of established B7-H3 knockdown Maver and Z138 xenografts slowed down compared with their NC groups by 59.1 and 65.0% at the end of observation, respectively. The similar growth inhibition of B7-H3-knockdown xenografts in glioma (22), breast cancer (26) and pancreatic cancer (23) has been observed in other reseach. Furthermore, we found that the expressions of Ki-67 and PCNA were significantly decreased in the B7-H3 silenced MCL xenografts.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The growth of established B7-H3 knockdown Maver and Z138 xenografts slowed down compared with their NC groups by 59.1 and 65.0% at the end of observation, respectively. The similar growth inhibition of B7-H3-knockdown xenografts in glioma (22), breast cancer (26) and pancreatic cancer (23) has been observed in other reseach. Furthermore, we found that the expressions of Ki-67 and PCNA were significantly decreased in the B7-H3 silenced MCL xenografts.…”
Section: Discussionsupporting
confidence: 82%
“…Tekle et al demonstrated that the B7-H3 silencing reduced metastatic capacity of MDA-MB-435 melanoma cells and significantly increased the survival of nude mice (20). Other studies also reported that B7-H3 was important in regulating the adhesive, migratory, and invasive capacity in breast cancer (21), glioblastoma (22), pancreatic cancer (23), prostate cancer (24) and osteosarcoma (25). Liu et al discovered that silencing of B7-H3 sensitized the breast cancer cell lines to paclitaxel by abrogating Jak2/Stat3 phosphorylation (26).…”
Section: Introductionmentioning
confidence: 99%
“…15 In human cancer, B7-H3 is detected on tumor cells arising from diverse tissues, and the expression level of B7-H3 is associated with increased disease severity. 16,17 B7-H3 can therefore function as either a T-cell co-stimulator or co-inhibitor depending on the biological context. 18 The exact role of B7-H3 in human cancer remains to be further delineated.…”
Section: Introductionmentioning
confidence: 99%
“…A172 shQPRT cells were generated by transfection with the Origene shQPRT vector (Origene). T325 glioma-initiating cells were generated as described previously (23). HA1800 primary astrocytes were obtained from ScienCell.…”
Section: Methodsmentioning
confidence: 99%